Akuntabilitas Pelayanan Publik Sektor Perizinan Dari Perspektif Balanced Scorecard (Studi pada Badan Pelayanan Perizinan Kabupaten Jombang) - Fitri, Ellia Aida (Jurnal Administrasi Publik, 2016)
Abstract :Accountability of Public Services Licensing Section from Balanced Scorecard Perspective (Study on Badan Pelayanan Perizinan Jombang Regency). The demand for public sector accountability related to the need for transparency and provision of information to the public in order to fulfill public rights. And many problems such as complicated procedures, the lack of certainty of time and settlement costs, brokering practices, and unprofessional services especially licensing service. Implementation accountability of public services on Badan Pelayanan Perizinan Jombang Regency using Balanced Scorecard perspectives, because the principles of Badan Pelayanan Perizinan Jombang Regency aims to optimize the service according to four perspectives of Balanced Scorecard. Result of the research shows that Badan Pelayanan Perizinan Jombang Regency already implementing the accountability ofpublic services using four perspectives of Balanced Scorecard. Total lack of resources, both facilities and infrastructures, as well as personnel, and lack of coordination between Tim Teknis and SKPD. These are creating obstacles for accountability of service. Keywords: Accountability, Public Service, Licensing Services, Balnced Scorecard   Abstrak: Akuntabilitas Pelayanan Publik Sektor Perizinan dari Perspektif Balanced Scorecard (Studi pada Badan Pelayanan Perizinan Kabupaten Jombang). Tuntutan adanya akuntabilitas sektor publik terkait perlunya dilakukan transparansi dan pemberian informasi kepada publik dalam rangka pemenuhan hak – hak publik. Dan banyaknya permasalahan seperti prosedur yang berbelit – belit, tidak adanya kepastian waktu dan biaya penyelesaiannya, praktik – praktik percaloan, serta pelayanan yang tidak profesional terutama pelayanan perizinan. Pelaksanaan akuntabilitas pelayanan pada Badan Pelayanan Perizinan Kabupaten Jombang menggunakan perspektif Balanced Scorecard, karena prinsip – prinsip Badan Pelayanan Perizinan Kabupaten Jombang bertujuan untuk mengoptimalkan pelayanan sesuai dengan empat perspektif Balanced Scorecard. Hasil penelitian menunjukan bahwa Badan Pelayanan Perizinan Kabupaten Jombang telah melaksanakan akuntabilitas pelayanan menggunakan empat perspektif Balanced Scorecard. Kurangnya jumlah sumberdaya baik prasarana dan sarana, maupun aparatur, serta kurangnya koordinasi antar Tim Teknis dan SKPD menjadikan penghambat jalannya akuntabilitas pelayanan.   Kata kunci: Akuntabilitas, Pelayanan Publik, Pelayanan Perizinan, Balnced Scorecard